Belt and Road Initiative Tiongkok di Indonesia: Studi Kasus Proyek Kereta Cepat Jakarta-Bandung - Ibrahim, Raihan (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
China's Belt and Road Initiative (BRI), launched in 2013, aims to improve global connectivity through infrastructure projects. In Indonesia, the Jakarta-Bandung High Speed Rail (KCJB) project is an important part of the BRI, with the aim of speeding up travel time, improving connectivity, and boosting regional economic growth. However, the project faces challenges such as land acquisition, community resistance, and the risk of economic dependence on China. Using the theoretical approaches of Dependency, International Political Economy, and National Interest, this study highlights the opportunities and risks of this project in the context ofVIndonesia-China bilateral relations. The analysis shows that the KCJB can deliver substantial benefits, but requires risk management, effective technology transfer, and an inclusive approach to ensure the project's success and sustainability.